The Role of The Government in Enforcing Mining Rehabilitation Laws: Environmental Law and Mining Law - Sudi Haryansyah; Rachmadi Usman; Muhammad Ananta Firdaus (Law and Justice research journal, 2025)
Mining activities in Indonesia result in significant environmental degradation, necessitating a robust legal framework for post-mining rehabilitation. However, enforcement is often hindered by normative overlaps between the Mining Law (No. 3/2020) and the Environmental Law (No. 32/2009), alongside a "supervisory vacuum" caused by recent centralization. This research evaluates the government's role in enforcing rehabilitation obligations and proposes a synchronized legal approach. Using a normative juridical method, the study identifies that authority fragmentation leads to a lack of accountability in reclamation fund management. Findings suggest that rehabilitation is frequently treated as a formal administrative procedure rather than a substantive ecological duty. Consequently, this study proposes a "Green Mining Governance" model that integrates environmental standards directly into mining permits (IUP) through a unified, inter-agency supervision system. This proposed framework integrates stringent environmental standards directly into the Mining Business Permit (IUP) and the annual Work Program and Budget (RKAB) through a unified, inter-agency supervision system. Such a reconstruction is essential to ensure that environmental restoration transcends formalistic requirements, evolving into a substantive legal obligation aimed at achieving long-term ecological justice and sustainable resource management.